RANCANG BANGUN SISTEM PAKAR DIAGNOSA GANGGUAN SUASANA PERASAAN (AFEKTIF) MENGGUNAKAN METODE TEOREMA BAYES BERBASIS ANDROID: Indonesia - nurdiana, nunu; Budiman, Budiman; whydiantoro, whydiantoro (Universitas Majalengka, 2021)
Feeling disorder a group of clinical features characterized by reduced or lost emotional control and self-control. Affective disorders can be depression, manic or a mixture of both (bipolar). Someone who has mood disorders needs treatment as early as possible through early detection and an accurate assessment is carried out in consultation with a psychologist. So a system is needed that can detect the possible disturbance of the mood. Expert systems are part of artificial intelligence that mimics the slow pace of an expert. Bayes' Theorem is a way of knowing conditional probabilities. Conditional probability is the probability of an event occurring, given that it has some relationship with one or more other events. The probability value of symptoms and disease is obtained based on the experience of an expert. This expert system can produce a process of diagnosing mood disorders with some data about mood disorders in the form of symptom data, disease data and its probability value. The accuracy rate is 100% using 10 test data. An expert system for diagnosing mood disorders which is designed to be an Android-based application of JavaScript and PHP as a programming language, Cordova as a framework for creating mobile applications, PHP 7.2.1 as a web server, MySQL 5.0.21 as a database.